2015
DOI: 10.24059/olj.v19i2.496
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction with Online Learning: Is it a Psychological Contract?

Abstract: The authors explore the possible relationship between student satisfaction with online learning and the theory of psychological contracts. The study incorporates latent trait models using the image analysis procedure and computation of Anderson and Rubin factors scores with contrasts for students who are satisfied, ambivalent, or dissatisfied with their online learning experiences. The findings identify three underlying satisfaction components: engaged learning, agency, and assessment. The factor score compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 59 publications
9
98
1
6
Order By: Relevance
“…Good learning materials are important because they can significantly increase student achievement and support student satisfaction with learning. These results are comparable with [16] and [6] who found that overall student satisfaction with online learning is significantly affected by how the course is organized and how the content is sequenced, the ease with which students can complete assignments, and the use of the system to engage students with content.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Good learning materials are important because they can significantly increase student achievement and support student satisfaction with learning. These results are comparable with [16] and [6] who found that overall student satisfaction with online learning is significantly affected by how the course is organized and how the content is sequenced, the ease with which students can complete assignments, and the use of the system to engage students with content.…”
Section: Discussionsupporting
confidence: 86%
“…In [16] authors, conducted a study, involving 1114 university students from southern Spain, to determine and analyze the main components influencing students' level of satisfaction with e-learning. The most relevant findings were that course design and contents, the facility for accessing and visualizing information on the teaching platform and the possibility of interaction were key aspects.…”
Section: B Lms and Students Satisfaction With Learningmentioning
confidence: 99%
“…However, the review found mixed data concerning student satisfaction outcomes [8]. Various studies on student satisfaction with online learning have identi ed the following factors: instructor interaction, communication, active learning, students' ability to initiate and control their actions in the learning environment, e cient assessment of academic progress, technology, and the learning environment [9,10].…”
Section: Distance Education and Student Satisfactionmentioning
confidence: 99%
“…Learner Satisfaction and experiences in e-learning environments Learner satisfaction and experiences are crucial elements that contribute to the quality and acceptance of e-learning in higher education institutions (Sampson et al 2010). Dziuban et al (2015) reported that the Online Learning Consortium (formerly known as Sloan Consortium) considered student satisfaction of online learning in higher education as an essential element to measure the quality of online courses. Different factors in uence learner satisfaction such as their digital literacy levels, their social and professional engagements, the learner support system including appropriate academic guidance and the course learning design (Allen et al 2002).…”
Section: Literature Reviewmentioning
confidence: 99%